Doing Conservation Differently: Toward a Diverse Conservations Inventory - Maris Gillette; Daniela Shebitz; Benedict Singleton (Ethnobiology Letters, 2023)
Many scientists and environmental activists argue that the scale and scope of contemporary conservation must increase dramatically if we are to halt biodiversity declines and sustain a healthy planet. Yet conservation as currently practiced has faced significant critique for its reliance on reductionist science, advocacy of “fortress”-like preservation measures that disproportionately harm marginalized communities, and integration into the global capitalist system that is the root cause of environmental degradation. The contributions to this special issue, developed from a panel at the Anthropology and Conservation conference co-hosted by the Royal Anthropological Institute and the Society of Ethnobiology in October 2021, collectively argue for what we, borrowing from Gibson-Graham’s diverse economies framework, call “doing conservation differently.” By bringing marginalized, hidden, and alternative conservation activities to light, researchers can contribute, in the spirit of Gibson-Graham’s work, to making these diverse conservations more real and credible as objects of policy and activism. This special issue contributes to inventorying the diverse conservations that already exist, which opens new spaces for ethical intervention and collective action.